Author Correction: Targeting wild-type KRAS-amplified gastroesophageal cancer through combined MEK and SHP2 inhibition. (October 2018) - Wong, Gabrielle; Zhou, Jin; Liu, Jie; Wu, Zhong; Xu, Xinsen; Li, Tianxia; Xu, David; Schumacher, Steven; Puschhof, Jens; McFarland, James; Zou, Charles; Dulak, Austin; et al.
In the Supplementary Information originally published with this article, a lane was missing in the β-actin blot in Supplementary Fig. 2. The lane has been added. The error has been corrected in the Supplementary Information associated with this article.